Neuronal Nitric Oxide Synthase (nNOS, NOS1) rs693534 and rs7977109 Variants and Risk for Migraine. Issue 9 (18th August 2015) - García‐Martín, Elena; Martínez, Carmen; Serrador, Mercedes; Alonso‐Navarro, Hortensia; Navacerrada, Francisco; García‐Albea, Esteban; Agúndez, José A.G.; Jiménez‐Jiménez, Félix Javier
<x xml:space="preserve">Abstract</x> Background/Objectives Many biochemical, pharmacological, neuropathological, and experimental data suggest a possible role of nitric oxide in the pathogenesis of migraine. We investigated the possible association between functional single nucleotide polymorphisms (SNPs) in the neuronal nitric oxide synthase gene (NOS1 or nNOS; chromosome 12q24.22) and the risk for migraine. Methods We studied the frequency of the of rs7977109 and rs693534 genotypes and allelic variants in 197 patients with migraine and 308 healthy controls using a TaqMan‐based qPCR assay. As a secondary analysis, we studied the possible influence of gender, age at onset of migraine, positive family history of migraine, and presence or absence of aura on the genotypes frequency. Results The frequencies of rs7977109 and rs693534 genotypes and allelic variants were not associated with the risk for migraine with OR for minor alleles = 0.94 (95% CI 0.72‐1.23) and = 0.88 (0.68‐1.15), respectively, and the lack of association was not influenced by gender, age at onset of migraine, positive family history of migraine, and presence or absence of aura. Conclusion NOS 1 rs7977109 and rs693534 genotypes and allelic variants are not associated with the risk for migraine in Caucasian Spanish people.